The Rekayasa Teknologi Konseling Kelompok dengan Relaksasi Otot Progresif dalam Menurunkan perubahan suasana hati (mood swing) pada lanjut usia di Panti Sosial Bina Insan Bangun Daya 2 Jakarta Timur - Nahampun, Mawi; Sukoco, Dwi Heru; Tukino, Tukino (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Group Counseling with Progressive Muscle Relaxation is the result of psychosocial therapy technology engineering in the form of modifying group counseling therapy steps to be more effective with the involvement of progressive muscle relaxation, namely stretching the physical muscles of the elderly who experience mood swing problems at the Bina Insan Bangun Daya 2 Social Home in East Jakarta. Group Counseling with Progressive Muscle Relaxation is used to deal with the problems of the elderly who experience mood swings during group counseling. This study aims to explain the implementation of group counseling therapy with progressive muscle relaxtation on reducing mood swings in the elderly. This study uses a Single Subject Design (SSD) type of A-B-A reversal. The subject in this study were JN, AF, and SL. The target behavior observed in this study during group counseling activities was related to changes in mood (mood swings) in the elderly, namely exticed conditions, feelings of fatigue, feelings of anger, and relaxed and calm conditions. The validity test of the research instrument used face validity and the reliability test used percent agreement. Then the data analysis used was visual data analysis consisting of analysis in conditions and between conditions. The results of the study indicate that Group Counseling Therapy with Progressive Muscle Relaxation has been proven to be able to reduce mood swings in the elderly, which means that Group Counseling Therapy with Progressive Muscle Relaxation has an effect on reducing mood swings in research subjects, which is known through data trend analysis with increasing and decreasing trends in the percentage of overlapping data in the analysis between conditions below 50% because the smaller the percentage of overlapping data, the stronger the influence of the intervension on changes in treatment.